Report of the Industrial Licensing Policy Inquiry Committee Appendices Volume IV - Planning Commission (Planning Commission, 1969)
The first major step taken by Government for covering the institutional gap in the capital market was the establishment of the Industrial Finance Corporation of India (IFCI). This was set up under the provisions of the IFCI Act, 1948, with a view to providing medium and long term credit to industry, especially when accommodation from normal financial sources was inappropriate or recourse to die capital market was impracticable. The main objective of setting up this institution was to cater to the financial requirements of the medium and large scale industries.
Government of India, Department of Industrial Development, Ministry of Industrial Development, Internal Trade and Company Affairs